Advancing in Employment: The Way Forward for Vocational Rehabilitation - Duncan, Grant (Victoria University of Wellington Law Review, 2004)
While the Injury Prevention, Rehabilitation, and Compensation Act 2001 reestablishes the ACC scheme on firmer foundations, there are still unanswered questions regarding the rights of individuals with permanent partial disability involving an incapacity for their previous occupation. While the existing entitlements appear to work well for the majority of injured workers, the basic goals set by legislation for vocational rehabilitation still allow the termination of support to be based upon a capacity for any suitable occupation, regardless of the availability of actual employment. No regard needs be given to claimants' longterm skill development or earning potential, let alone to their aspirations to advance themselves in employment. We do not yet fully understand what effect the present vocational rehabilitation provisions are having on claimants' incomes and sustainable employment. In a policy environment that stresses the need for a highskill, highproductivity economy, and that seeks not to widen social inequalities, the present rehabilitation goals seem inconsistent. Further, it will be shown that they do not meet International Labour Organisation (ILO) standards.